cho P = l2a-1l -(a-5) rút gọn P
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) A = |x - 1| - (2x - 5)
+) x >= 1 => x - 1 >= 0 => |x - 1| = x - 1
Khi đó A trở thành:
A = (x - 1) - (2x - 5) = x - 1 - 2x + 5 = -x - 4 = -(x + 4)
+) x < 1 => x - 1 < 0 => |x - 1| = 1 - x
Khi đó A trở thành:
A = (1 - x) - (2x - 5) = 1 - x - 2x + 5 = 6 - 3x
![](https://rs.olm.vn/images/avt/0.png?1311)
a) + Với \(x< \frac{1}{3}\) thì |3x - 1| = 1 - 3x; |5 - x| = 5 - x
Ta có:
A = 2.(1 - 3x) - (5 - x)
A = 2 - 6x - 5 + x
A = -3 - 5x
+ Với \(\frac{1}{3}\le x< 5\) thì |3x - 1| = 3x - 1; |5 - x| = 5 - x
Ta có:
A = 2.(3x - 1) - (5 - x)
A = 6x - 2 - 5 + x
A = 7x - 7
+ Với \(x\ge5\) thì |3x - 1| = 3x - 1; |5 - x| = x - 5
Ta có:
A = 2.(3x - 1) - (x - 5)
A = 6x - 2 - x + 5
A = 5x + 3
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\text{1)}\hept{\begin{cases}A=2x-3-3x+1=-x-2\\A=2x-3+3x-1=5x-4\end{cases}}\)
\(\text{2)}\hept{\begin{cases}A=-x-2=4\\A=5x-4=4\end{cases}\Rightarrow\hept{\begin{cases}x=-6\\x=\frac{8}{5}\end{cases}}}\)
\(\text{3)}\hept{\begin{cases}A=-2-2=-4\\A=5\times2-4=6\end{cases}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(=\frac{x-x+2}{x^2-4}:\frac{1-x+2}{x-2}\)ĐKXĐ:x\(\ne+-2\)
\(=\frac{2}{x^2-4}.\frac{x-2}{3-x}=\frac{2}{\left(x+2\right)\left(3-x\right)}\)
=\(\frac{2}{-x^2-x+6}\)